Industrial Growth in the Integrated European Economic Space - Tsiapa, Maria (Organizations and Markets in Emerging Economies, 2014)
The European space has experienced relentless geo-economic changes that result in a re-conceptualisation of their industrial growth pattern. The aim of this paper is to empirically detect the determinants of industrial growth covering the entirety of Europe, thus embracing economies of different production systems and welfare levels. Integration has influenced the economies and their industrial growth not only inside the EU but inside the whole European area, on the one hand, by attributing to them common behavioural characteristics, and on the other hand, by forming their industrial growth pattern under the influence of different natural factors in alignment with the regions’ comparative advantage and the markets’ maturity levels.
Keywords: industrial growth; Europe; integration; productive systems